On Friendship between the No Longer and the Not Yet An Ethnographic Account: Cairo Papers in Social Science Vol. 35, No. 4. - Mohsen, Soha (Cairo papers in social science., 2020)
Against a backdrop of conditions of precarity and the ruins of finance capitalism, this study examines the manifestations of how the relationship of friendship manages to re-invent and re-define itself. Moreover, it asks whether new modes of relationality, companionship, and intimacy can be cultivated and practiced given the current neoliberal conditions of living. The questions that this study attempts to open up are focused on the re-workings, reconfigurations, and re-makings of practices of sociality and intimacy between friends.